Prototipo para la Evaluación de Calidad de Servicio Mediante Técnicas de Encolamiento en Ambientes de Backbone - Aparicio Pico, Lilia Edith; Hernández Riaño, Velssy Liliana; Sierra Hernández, Fredy A. (Ingeniería, 2006)
The cost in infraestructure and access to emerging technologies on telecommunications networks, made necessary to have a mechanisms the quality of service assessment using queuening based. Objective in this article was evaluate different technical modeled various scenes of campus backbone network, in order to compare his performance using the tool of simulation OPNET. The evaluation aimed to the measurement of keys variables in the performance networks like delay, packet loss and jitter, among others. Are show here the results once these were gotten from utilization mechanism when granting differentiation to sensitive traffics to present factors of congestion in IP networks, such like traffic in real time; collecting a significant improvement in the network performance.